OLHA (Nα-oleoylhistamine) modulates activity of mouse brain histaminergic neurons. (1st September 2022) - Sergeeva, Olga A.; Mazur, Karolina; Reiner-Link, David; Lutsenko, Kiril; Haas, Helmut L.; Alfonso-Prieto, Mercedes; Stark, Holger
Abstract: Histaminergic (HA) neurons are located in the tuberomamillary nucleus (TMN) of the posterior hypothalamus, from where they project throughout the whole brain to control wakefulness. We examined the effects of N α -oleoylhistamine (OLHA), a non-enzymatic condensation product of oleic acid (OLA) and histamine, on activity of mouse HA neurons in brain slices. OLHA bidirectionally modulated the firing of HA neurons. At 10 nM OLHA inhibited or had no action, whereas at 1 μM it evoked excitatory and inhibitory responses. Inhibition was not seen in presence of the histamine receptor H3 (H3 R) antagonist clobenpropit and in calcium-free medium. Pre-incubation with a histamine-reuptake blocker prevented the decrease in firing by OLHA. OLHA-evoked increase in firing (EC50 ∼44 nM) was insensitive to blockers of cannabinoid 1 and 2 receptors and of the capsaicin receptor, but was significantly impaired by the peroxisome proliferator-activated receptor-alpha (PPAR-alpha) antagonist MK886, which suppressed also the rise in intracellular calcium level caused by OLHA. The OLHA-evoked excitation was mimicked by synthetic PPAR-alpha agonists (gemfibrozil and GW7647) and was abolished by the PKA inhibitor H-89. The H3 R affinity (Ki) for histamine, measured in HEK293 cells with stable expression of human H3 R, was higher than for OLHA (Ki: 42 vs 310 nM, respectively). Expression of PPAR-alpha was not different between TMN regions of males and females, responses to OLHA did not differ. Molecular modelling of PPAR-alpha bound to either OLHA or OEA showed similar binding energies. These findings shed light on a novel biotransformation product of histamine which may play a role in health and disease. Highlights: OLHA bidirectionally modulates histaminergic neuron firing. Histamine 3 receptor and PPAR-alpha are involved in inhibition and excitation respectively. OLHA interacts with histamine reuptake and may modulate histaminergic transmission under pathological conditions.